Carbon dating of Qur’anic manuscripts: Analytical review - Sadia Yousaf zia; DR. Muhammad Samiullah (jihat-ul-islam, 2023)
The Qur'an is one of the oldest and historical books in the world, which has astonished the whole world. The history of pottery, sculptures and manuscripts has long history been determined by radiography. This technique has enhanced by radioactive radiography. Therefore, this method is also applied on Qur’anic manuscripts to determine its original existing date. Different molecules and compounds are present on the planet with their radioactive isotopes that emit certain rays like beta and Gemma rays. Naturally, carbon 14 isotopes are radioactive carbon. The other two isotope are not radioactive are C12 and C13.Carbon is an element that has the properties that it is a component of organic matter and if it is radioactive then it can be present in it for a long time. Its life can be estimated from the amount of carbon in it. Carbon isotope have its half-life of 5370 years with which we determine the life of the object. There are various methods for its historical determination, which are called radiometric dating. There are various technical methods of which the most accurate method is accelerator mass spectrometry, which is widely used. Samples are used not only in small but also in the short term to get accurate results. An overview of the above method and an analytical study of the results obtained from it is actually the main topic of discussion. Greatness is measured. This study proves that the Qur'an is relatively safe and consistent with the previous inspired books. There is also a comparative study of the Qur'an manuscripts samples. The real purpose is Analytical study of this research.